Effects of spontaneous otoacoustic emissions on frequency discrimination - Hansen, Rói; Santurette, Sébastien; Verhulst, Sarah (Proceedings of Meetings on Acoustics, 2013)
When an external tone is presented in proximity to the frequency of a spontaneous otoacoustic emission (SOAE), the SOAE typically synchronizes to the external tone, a phenomenon known as "entrainment". As the tone moves further away from the SOAE frequency, beating patterns between the SOAE and the pure tone occur (Long, Hear. Res. 119, 1998). This study investigated perceptual consequences of SOAE beating and entrainment on the frequency difference limen (FDL), which has been found to improve near an SOAE. SOAE entrainment patterns were obtained for six subjects with a strong SOAE in the ipsilateral ear and no SOAE in the corresponding frequency range of the contralateral ear. Hearing thresholds and FDLs were measured ipsi- and contralaterally for nine frequencies covering the entrainment and beating regions of the SOAE. FDLs systematically improved in the entrainment region, worsened when beating occurred, and improved again for frequencies further away from the SOAE. No improvement in FDL was found in any of the contralateral ears tested, suggesting that the effect is of peripheral, rather than of central, origin. The results contradict an earlier hypothesis stating that FDL performance near SOAE frequencies is governed by a central oversensitivity to the SOAE frequency.